Prognostic value of metformin treatment characteristics for vitamin B12 deficiency among patients with type 2 diabetes mellitus - Thuy, Nguyen Thanh; Chi, Le Van; Hoang, Lam Van (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2026)
Background: Long-term treatment of diabetes mellitus with metformin is associated with an increased risk of vitamin B12 deficiency. This study aims to describe the prevalence of vitamin B12 deficiency in patients with type 2 diabetes mellitus (T2DM) treated with metformin-containing regimens compared with newly diagnosed patients, and to determine the diagnostic performance of metformin treatment characteristics for vitamin B12 deficiency. Methods: This cross-sectional study included 579 patients with T2DM aged 18 - 60 years: 283 patients receiving continuous metformin treatment for ≥ 6 months (patient group) and 296 newly diagnosed patients not yet treated with glucose-lowering medications (reference group). The study was conducted at the Outpatient Department of Cho Ray Hospital from January 2024 to August 2025. Receiver operating characteristic (ROC) analysis was used to evaluate the diagnostic performance for vitamin B12 deficiency. Results: The prevalence of vitamin B12 deficiency in the patient group was 14.1%, which was markedly higher than in the reference group (0.3%). The mean serum vitamin B12 concentration in the patient group was 484.16 ± 202.80 pg/mL, lower than that in the reference group (666.94 ± 85.38 pg/mL). A metformin treatment duration exceeding 4.83 years and a metformin use index (MUI) greater than 8 showed high diagnostic performance for vitamin B12 deficiency, with AUCs of 0.921 and 0.901, respectively, whereas metformin dose was not diagnostically significant. Conclusion: Patients with T2DM treated with metformin longer than 4.83 years and have metformin usage index (MUI) greater than 8 should undergo early screening for vitamin B12 deficiency to reduce treatment-related complications and to improve the comprehensive management of T2DM.